2015
DOI: 10.1111/ijfs.12689
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of soya bean oil bleaching by ultrasonic processing and investigate the physico‐chemical properties of bleached soya bean oil

Abstract: Summary In this study, an ultrasonic bleaching method for soya bean oil under different conditions was optimised by monitoring the reduction of oil‐containing colourants. Ultrasonic power, clay content, temperature and time had a significant interaction effect on (P < 0.05) the reduction of oil pigments and colourants. Under optimised conditions, red and yellow colour indices in the ultrasound‐bleached soya bean oil reduced to 74.44% and 75.55%, and 54.18% and 58.85%, respectively, at amplitudes of 85% and 65%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 24 publications
2
40
0
3
Order By: Relevance
“…Their findings proved that the fatty acid composition of the vegetable oils does not change after ultrasonic treatment (Chemat et al 2004). Also, Abedi et al (2015) showed that the ultrasonic process did not alter the fatty acid profile and no significant difference between the bleached oil under ultrasonic and control processes were observed. Therefore, it could be concluded that ultrasonic waves will have no destructive effects on the fatty acid compositions if the applied condition of sonication was controlled.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Their findings proved that the fatty acid composition of the vegetable oils does not change after ultrasonic treatment (Chemat et al 2004). Also, Abedi et al (2015) showed that the ultrasonic process did not alter the fatty acid profile and no significant difference between the bleached oil under ultrasonic and control processes were observed. Therefore, it could be concluded that ultrasonic waves will have no destructive effects on the fatty acid compositions if the applied condition of sonication was controlled.…”
Section: Discussionmentioning
confidence: 94%
“…It can be concluded that the ultrasonic methods had been completely effective in removal of the red and yellow colors in the examined oil samples and its impact is more significant in olive oil than in sunflower oil. According to the American trading rules, maximum 2.5 red and 25 yellow units are the acceptable colors units for the bleached oils (Rossell and Pritchard 1991;Abedi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations